2019
DOI: 10.1177/0093854819846917
|View full text |Cite
|
Sign up to set email alerts
|

The School-To-Prison Pipeline: An Examination of the Association Between Suspension and Justice System Involvement

Abstract: The purpose of this study is to contribute to understanding the school-to-prison pipeline by examining the extent to which low school commitment and deviant peer association mediate the relationship between suspension by age 12 and justice system involvement by age 18. The analysis was performed in two steps using structural equation modeling and data from the LONGSCAN study ( N = 837). Results of the full model indicate that suspension by the age of 12 is associated with justice system involvement directly an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…These costs are potentially formidable and might accumulate over time, leading to lower educational attainment or earlier involvement in the criminal justice system (Wolf and Kupchik 2017). Indeed, being suspended from school has been associated with decreased school engagement (Pyne 2019) and increased association with deviant peers (Novak 2019;Hemphill et al 2012) and increased antisocial behavior (Hemphill et. al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These costs are potentially formidable and might accumulate over time, leading to lower educational attainment or earlier involvement in the criminal justice system (Wolf and Kupchik 2017). Indeed, being suspended from school has been associated with decreased school engagement (Pyne 2019) and increased association with deviant peers (Novak 2019;Hemphill et al 2012) and increased antisocial behavior (Hemphill et. al.…”
mentioning
confidence: 99%
“…al., 2012). Scholars have in turn hypothesized these factors serve as mechanisms by which suspension can lead to criminal justice involvement (Novak 2019;Hemphill 2012;Moore and McArthur 2014;Skiba, Arredondo, and Williams 2014).…”
mentioning
confidence: 99%
“…However, interpreting our results may not be this straightforward. In a recent study examining the moderating mechanism by which suspended students become involved in the criminal justice system, Novak (2019) found that school commitment was not affected directly by suspension but indirectly through deviant peers. Students who were suspended by age 12 were more likely to associate with deviant peers, and deviant peers predicted justice system involvement by age 18.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few studies that have assessed the potential moderating or mediating mechanisms between exclusions and criminality, it seems that suspended students may turn to deviance following an increase in deviant peer relationships. Novak (2019) assessed both school commitment and deviant peer exposure and found that only deviant peer exposure predicted later justice system involvement. Although school commitment was not significant in this study, in contrast to the hypothesis put forth by the present study, it is possible this was a result of the measures used.…”
Section: Discussionmentioning
confidence: 99%